Delineation of motor and somatosensory thalamic subregions utilizing probabilistic diffusion tractography and electrophysiology. Issue 3 (11th October 2012) - Sudhyadhom, Atchar; McGregor, Keith; Okun, Michael S.; Foote, Kelly D.; Trinastic, Jonathan; Crosson, Bruce; Bova, Frank J.
Abstract Purpose: To employ and compare probabilistic diffusion tractography (PDT) for the explicit localization of connections from the thalamus to somatosensory cortex (S1) and primary motor cortex (M1) / supplementary motor area (SMA) with microelectrode electrophysiology in patients undergoing deep brain stimulation (DBS) surgery. Materials and Methods: These tractography‐derived connections were used to categorize voxels in the thalamus as corresponding to sensory or motor physiology. A novel model (referred to in this work as the "mixture" model) to delineate PDT‐based thalamic functional subregions by thresholding fiber intensities, ie, connectivity‐defined regions (CDR), was devised. Regions created using this classification method were compared with the most commonly used model (referred to in this work as the "separation" or "winner takes all" model) for defining CDRs. Results: Electrophysiology data corresponded better for S1 CDRs created using the mixture model for both sensory and motor cells. Separation model CDRs showed poor correspondence against electrophysiology, with few sensory cells corresponding to the S1 separation model CDR. Conclusion: Mixture model‐based CDRs may offer a significant improvement in delineation of functional subregions of subcortical structures. J. Magn. Reson. Imaging 2013;37:600–609. © 2012 Wiley Periodicals, Inc.